Investigating Morphological Process of Payandra on Javanese Metaphor - Dwi Astuti Wahyu Nurhayati (Yayasan Visi Intan Permata, 2016)
This article examines morphological process on payandra used by pranata adiacara. This study was done through a survey to pranata adiacara in Trenggalek and Tulungagung surroundings, small districts in East Java- Indonesia, in order to get underlying basis of processes of morphological on Javanese style which are influential toward their language style used in Javanese marriage ceremonies. The instrument- interview & documentation were developed in accordance to get the morphological processes and payandra used by pranata adiacara. The study reveals that payandra and processes of morphological on Javanese style used by pranata adiacara are divided into including 2 two main types: 1) Affixation (a. Internal change, b.Prefixation ; 2) Non Affixation: a.Compounding, b.Borrowing, c. Blending, d.Backformation, e. Reduplication, f. Clipping and the words used by pranata adiacara in sentences. Finally, the results of this study offers language phenomena arises because of some reasons which are mainly useful for those conducting communication among pranata adiacara and the audiences to figure out how beautiful and handsome of the bridge and bridgroom and the values of wishes in conducting traditional ceremonies and those who are concerned in investigating panyandra words and metaphors used by pranata adiacara or other varities as well as suggestions for future research.